Biodiesel production via single - step alkali catalyst in batch process - Nurul Farha, Abdul Rashid (2008)
Biodiesel is an alternative fuel, produced from domestic and renewable resources. Biodiesel is biodegradable, non-toxic, and essentially free of sulfur and aromatics. Biodiesel is made through a chemical process called transesterification whereby the glycerin, it’s by product is separated from the fat or vegetable oil and sold to produce products such as soaps and grease. The main objective of this research is to produce the biodiesel from waste cooking oil and to optimize the production by using Design of Experiment (DOE). The single step alkali catalyzed process was adopted to prepare biodiesel by transesterification process by using the methanol and homogenous alkali catalyst, sodium hydroxide. The products was analyzed to determine the yield, concentration of methyl ester and moisture content to get the catalyst concentration and time at optimum condition by using DOE. From DOE it is found that the optimum condition to get the higher value of yield percentage was suggestion from RSM by the model equation is 56.31% with the reaction time is 30.37 minutes and catalyst concentration is 1.08%. For methyl ester concentration percentage, RSM suggested by the model equation is 77.96% with the reaction time is 30.24 minutes and catalyst concentration is 0.58%.